Congenital heart disease - a public health problem - Marioara Boia; Oana-Cristina Costescu; Daniela Cioboata; Anca Popoiu; Nicoleta Lungu; Florina Doandes; Aniko Maria Manea (Amaltea Medical Publishing House, 2020)
Introduction. A congenital heart disease is a defect in the structure of the heart or great vessels that is present at birth. Signs and symptoms depend on the specific type of defect. The cause of a congenital heart defect is often unknown but remain the most common congenital malformations in newborns and infants with a major role in early and late neonatal morbidity and mortality. Material and methods. The study was carried out in the Department of Neonatology and Premature in the collaboration with the Department of Pediatric Cardiology, from the Clinical Emergency Hospital for Children Louis Țurcanu Timișoara, in a period of 3 years (2015- 2018). There were 70 patients included in the study, who presented congenital heart malformation diagnosed clinically, by ultrasound and Angio-CT. Results. The incidence of cardiac malformations in our unit was 2.11%. The most common clinical signs encountered in patients with congenital heart disease were dyspnea associated with cyanosis, systolic murmur and oxygen saturation oscillations (SaO2). Associated with pregnancy, the presence of teratogenic factors with possible implication in congenital heart malformations was also detected. There were 12 cases involved genetic syndromes, Down's syndrome having the highest prevalence. Due to the complexity of the cardiac malformation in the studied group, 11 patients (15.71%) died. Conclusions. Congenital cardiovascular malformations are a problem of public health. In the assessment of a newborn with cardiac pathology, there should be involved obstetricians, neonatologists, anesthetists, pediatric cardiologists, pediatric cardiovascular surgeons, geneticists, with the common goal of preventing, diagnosing, monitoring and treating congenital heart abnormalities.